2022
DOI: 10.3390/nano12132148
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in the Remediation of Persistent Organic Pollutants Using Nanomaterials and Related Processes: A Review

Abstract: Persistent organic pollutants (POPs) have become a major global concern due to their large amount of utilization every year and their calcitrant nature. Due to their continuous utilization and calcitrant nature, it has led to several environmental hazards. The conventional approaches are expensive, less efficient, laborious, time-consuming, and expensive. Therefore, here in this review the authors suggest the shortcomings of conventional techniques by using nanoparticles and nanotechnology. Nanotechnology has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 157 publications
0
17
0
Order By: Relevance
“…Organic pollutants are persistent longer in the environment and their bioaccumulation and pervasiveness makes them highly toxic to aquatic life, including humans, plants, and animals [1]. Methylene blue dye is one of the persistent organic pollutants released by the textile industries along with sewage to water sources and other environments.…”
Section: Introductionmentioning
confidence: 99%
“…Organic pollutants are persistent longer in the environment and their bioaccumulation and pervasiveness makes them highly toxic to aquatic life, including humans, plants, and animals [1]. Methylene blue dye is one of the persistent organic pollutants released by the textile industries along with sewage to water sources and other environments.…”
Section: Introductionmentioning
confidence: 99%
“…Many functional groups like carboxy, carbonyl, hydroxy, phosphoryl, and amide groups are present in algal cell walls, which help in dye decolorization [126]. In another investigation, Mahajan et al [127] reported 70-100% decolorization of methyl red dye at pH 3.5-9.5 using Chara vulgaris L. In another study by Boulkhessaim et al [128], they reported 45-80% decolorization of dyes using Chlorella vulgaris, whereas Dellamatrice et al [129] observed 91% dye decolorization using Cyanobacterium phormidium. In another study, Alprol et al [130] found 75.7% and 61.11% decolorization of dyes by using Arthrospira platensis complete dry biomass and lipid-free biomass.…”
Section: Phycoremediationmentioning
confidence: 99%
“…Much has been written in the literature about heterojunction photocatalysts for wastewater treatment because of their unique properties such as ease of fabrication, low cost, chemical stability, and non-toxicity [ 13 15 ]. However, heterojunction photocatalysts have some drawbacks that limit their practical application such as rapid recombination of charge carriers and limited absorption of visible light, which reduces the photocatalytic efficiency [ 16 , 17 ]. Therefore, the photocatalytic efficiency of the heterojunction photocatalyst can be greatly improved by coating the photocatalyst surface with metal nanoparticles (NPs) as plasmonic materials known as plasmonic-based heterojunction photocatalysts [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%